The Effect of a Teacher-led Nutrition Education Program towards Nutrition and Anemia Status of Adolescent Girls in Bogor, Indonesia - Rachman, Purnawati Hustina; Ekawidyani, Karina Rahmadia; Mauludyani, Anna Vipta Resti; Februhartanty, Judhiastuty (Lembaga Penerbitan Unversitas Esa Unggul, 2021)
Nutrition education among adolescents is lacking in Indonesian schools. Whereas adolescent girls, in particular, need adequate nutrients to prepare them for their future pregnancy which may improve their nutrition status in the long term. Therefore, this study aims to assess the impact of a teacher-led nutrition education program on the nutrition and anemia status of adolescent girls. A quasi-experimental design was applied in junior high and high schools in Bogor which compared the findings between the intervention (n=112) and the control group (n=129). Teachers in the intervention group received training on health and nutrition for adolescents and were asked to deliver nutrition education for their students for 14 weeks. The control group did not receive any exposure to the topics. The weight, height, and hemoglobin level were measured before and after the program. Paired and independent t-test statistical analysis was used to assess the impact of the intervention for continuous variables and the Chi-Square test was used for categorical data. After the program, although there were no significant improvements in BMI-for-age z-score, however, significant improvements were observed for hemoglobin level among the treatment group. This was consequently shown in the anemia status, where the prevalence of anemia was significantly lower compared to the control group (p<0.001). The findings demonstrate that teacher-led nutrition education can improve the anemia status of adolescent girls.